The cost efficiency of German banks: a comparison of SFA and DEA - Michael Koetter; Alexander Karmann; Elisabetta Fiorentino (Deutsche Bundesbank, 2006)
We investigate the consistency of efficiency scores derived with two competing frontier methods in the financial economics literature: Stochastic Frontier and Data Envelopment Analysis. We sample 34,192 observations for all German universal banks and analyze whether efficiency measures yield consistent results according to five criteria between 1993 and 2004: levels, rankings, identification of extreme performers, stability over time and correlation to standard accounting-based measures of performance. We find that non-parametric methods are particularly sensitive to measurement error and outliers. Furthermore, our results show that accounting for systematic differences among commercial, cooperative and savings banks is important to avoid misinterpretation about the status of efficiency of the total banking sector. Finally, despite ongoing fundamental changes in Europe?s largest banking system, efficiency rank stability is very high in the short run. However, we also find that annually estimated efficiency scores are markedly less stable over a period of twelve years, in particular for parametric methods. Thus, the implicit assumption of serial independence of bank production in most methods has an important influence on obtained efficiency rankings.
Keywords: L25; G21; D24; 330; Cost Efficiency; Banks; Stochastic Frontier Approach; Data Envelopment Analysis; Bank; Kostenfunktion; Technische Effizienz; Data-Envelopment-Analyse; Schätzung; Deutschland